TRABALHO INTERDISCIPLINAR ENTRE PROFISSIONAIS DE EQUIPES DE ESTRATÉGIA SAÚDE DA FAMÍLIA DAS 4ª E 5ª REGIONAIS DE SAÚDE DO PARANÁ: UMA INVESTIGAÇÃO QUALITATIVA - Justus Neto, Altair (2016)
The interdisciplinary approach is characterized by the interaction of several disciplines working within the same project. Considering health, it should be interpreted as a way to approach certain situations or problems, articulating different knowledge and practices, integrating the team and improving care provided to the population. The objective of this study was to analyze, using a qualitative methodology the existence of interdisciplinary work between Health Strategy Teams of family professionals (HST) from 4th and 5th Regional Health Bureau of the State of Paraná. To obtain the data, it was applied the conversation circle technique that aimed to generate a discussion among professionals of the HST about interdisciplinarity. The participants were 31 employees, belonging to five professional categories, distributed in two urban HST from Guarapuava, PR and two urban HST from Irati, PR. Four categories relating to units of meaning were observed: a) knowledge about interdisciplinarity: workers understand the subject as an exchange of information, association or combination of professionals and multidisciplinary work; b) interdisciplinary practices: participants mentioned the transfer of information, group discussion, the professional association, and the team meetings as actions taken to promote interdisciplinarity. Moreover, they observed the absence of interdisciplinary practices; c) difficulties in carrying out interdisciplinary work: the lack of communication between the different levels of management, inadequate physical structure in the health units, the lack of human and material resources and staff turnover as difficulties to carry out interdisciplinary work were listed; d) practices undertaken for the promotion of interdisciplinary work: it was reported that the incentive for these actions should be done only by managers. Furthermore, the professionals admit that there are some booster interventions; nevertheless, they were unable to specify which they are. We conclude that the professionals have a fragmented knowledge of interdisciplinary and have a low level of understanding of the interdisciplinary practices carried out by professionals from the HST. Besides that, it was observed that there are many difficulties for the realization of interdisciplinary practices in HST and that teams believe that only senior public managers are the responsible for encouraging and providing new knowledge to the teams.